Corporate Legal Liability for Environmental Damage - Utiarahman, Nuraisah Masita (Estudiante Law Journal, 2025)
This study aims to examine the legal liability of companies for environmental damage and its implications for financing sustainable education. The main focus of this study is to understand how companies can contribute through Corporate Social Responsibility (CSR) programs that support sustainability based education initiatives, and to identify challenges and opportunities in their implementation. The method used in this study is a literature study, by reviewing various related regulations, including Law No. 32 of 2009 and Government Regulation No. 27 of 2012. This study also uses a qualitative approach to analyze the implementation of corporate CSR programs in the sustainable education sector, as well as the challenges faced in implementing this policy. This study found that corporate legal liability for environmental damage can be utilized to fund sustainable education through CSR. Companies can contribute by providing funds for curriculum development, environmentally friendly educational facilities, and training that increases environmental awareness. However, the main challenge found is the lack of clear regulations regarding the use of CSR funds for education that supports sustainability. Clearer policies are needed to ensure that corporate contributions are more focused and impactful